Roman Amphoras from Anchialus (preliminary report) - Rusev, Nikolay (Rei Cretariae Romanae Fautorum Acta, 2022)
The aim of this paper is first to try to describe the Roman amphorae from Anchialus. The defined amphoras are from the Eastern Mediterranean, the Aegean and the Pontic area. The earliest artifact are pieces of Camulodunum type 184 and Peacock/ Williams Class 9 dated to the 1st century AD-first half of the 2nd century AD. During the 2nd century, there is a graudal increase in the number of vessels. The most intensive period of importation is the second half of the 2nd-3rd century AD. After this period, the identified types are Zeest 80 type and Kapitän II which show trade and contacts of Anchialus after the middle of the 3rd century and the early part of the Late Roman period. A small group of the so called 'table amphora' was also recorded. The amphoras are from well-researched complexes and they are a clear source for the economy of the one of the most important ancient cities in the territory of modern Bulgarian territory. The vessels found on the site of Anchialus show that the highest proportion of imported of goods had their origin in the Black Sea region, followed by imports from western Asia Minor and North Aegean region. The imported products were olive oil, fish sauce and wine with a predominance of wine and olive oil amphoras.